State Immunity or State Impunity? Human Rights and State Immunity Revisited in the ICJ’s Judgment on the Case of the Jurisdictional Immunities of a State - Gerlich, Olga (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The paper aims to comment on the judgment of the International Court of Justice of 2nd February 2012 in the case of Jurisdictional Immunities of the State between Germany and Italy from the perspective of the problem of jurisdictional immunity. In its decision concerning compensation for atrocities suffered by Italian citizens during World War  II granted by Italian courts against the German State as well as the execution of the analogical decisions of Greek courts, the International Court of Justice upheld the immunity of the German State. The compensation sought by the plaintiffs in the national proceedings was to redress massacres on the civil population, deportations and forced labour. In its decision the Court analyzed the exception proposed by Italy in three strands which, according to the Respondent, cumulatively would result in an exception to the rule of state immunity. Firstly, the acts giving rise to the Italian claims constituted grave violations of humanitarian law; secondly, the rules of law violated constitute peremptory norms of international law; thirdly, no other form of redress was available rendering the exercise of jurisdiction by the Italian court to be a measure of a last resort for the victims.